Estado y agricultura familiar: interpelar las racionalidades y situar lo comunitario en Río Negro, Argentina - Michel, Carolina (2025)
In this article, we propose to reflect on the ways in which the State conditions, produces or relieves the subjects of the Family Farming in northern Patagonia to carry out interventions in the rural world, paying attention to the displacements of meaning that occur in this process. To achieve this, we investigate two planning tools for the representation and design of territories: agricultural censuses and the Sheep Law. We critically analyze these tools in light of testimonies from members of a Mapuche pastoral community in the steppe region. Our findings highlight the State's performative role in constructing subjects that fit the objectives of rural development policies, as well as the community's ability to resist and reinterpret both current and historical state orders. We conclude that the State must reconsider the community as a vital dimension of both analysis and intervention.